Design of an anechoic chamber for W-Band and mmWave - Pinho, Pedro (2021)
In this paper, we describe the design of an electrically large anechoic chamber for usage on millimetre-wave bands. Ansys Savant sotware was used to perform a simulation of the chamber, using physical optics coupled with uniform theory of diffraction (PO/UTD). Moreover, a method based on an open waveguide probe is described in this paper to obtain the electrical properties of the RF absorbers at millimetre-wave frequencies. Two different source antennas were simulated in this work and the corresponding quiet zones predicted. The largest quiet zone was 30 mm x 30 mm x 50mm, for a chamber size of 1.2 m x 0.6 m x 0.6 m.